Предмет: Алгебра,
автор: Streltsova
6 + ( 2 - 4 х )+ 5 = 3 ( 1 - 3 х )
Ответы
Автор ответа:
0
6+2-4x+5=3-9x
13-4x=3-9x
-4x+9x=3-13
5x=-10
x=-10/5
x=-2
13-4x=3-9x
-4x+9x=3-13
5x=-10
x=-10/5
x=-2
Автор ответа:
0
Спасибо)))
Автор ответа:
0
6+2-4х+5=3-9х
9х-4х=3-6-2-5
5х=-10
х=-10:5
х=-2
Ответ:-2
9х-4х=3-6-2-5
5х=-10
х=-10:5
х=-2
Ответ:-2
Автор ответа:
0
Спасибо)))
Похожие вопросы
Предмет: Английский язык,
автор: mshj4kpk2z
Предмет: Геометрия,
автор: krylach11
Предмет: Английский язык,
автор: Riwit
Предмет: Биология,
автор: shalyndoc
Предмет: Литература,
автор: Yana7689